A Study of Baumeister’s Self Defining Process in The Blind Assassin - Fatima Batool; Meher - ul - Nissa; Asia Khan (Linguistics and Literature Review, 2018)
This paper explores the novel The Blind Assassin through the lens of Baumeister’s self-defining process. Identity, being an interpretation of self, lies in persistence and consistence over time. Identity crisis is the inability to define basic values, long-term goals and major affiliations, all of which help a person in the process of self-defining. The Blind Assassin being the story of two sisters, Iris Griffen and Laura Griffen, is helpful in developing a comparison of the two characters who are subjected to same upbringing and same social surroundings. The elder sister manages to assert her will in a competitive society while the younger one suffers from identity crisis and finds solace in suicide. Baumeister’s model of identity provides basis to interpret the inability of Laura in defining herself. The more a person is socially compatible the more she is at ease with herself. Her biological, social and sexual needs never addressed, however, she keeps trying to make choices and struggles to realize her potential. She ends up discontented as she is taken as an eccentric and dissatisfied as her own sister gives her the greatest shock of her life. The more a person is allowed to make choices the more successful she is in defining herself. Laura completes her self-defining process by driving off the bridge which Freud interprets as a way of giving birth. This paper helps understanding the ways in which society particularly family affect an individual’s decisions and the ways in which an individual tries to assert her/his will.